2022
DOI: 10.1038/s41586-022-05049-6
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater sequencing reveals early cryptic SARS-CoV-2 variant transmission

Abstract: As SARS-CoV-2 continues to spread and evolve, detecting emerging variants early is critical for public health interventions. Inferring lineage prevalence by clinical testing is infeasible at scale, especially in areas with limited resources, participation, or testing and/or sequencing capacity, which can also introduce biases1–3. SARS-CoV-2 RNA concentration in wastewater successfully tracks regional infection dynamics and provides less biased abundance estimates than clinical testing4,5. Tracking virus genomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
216
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(255 citation statements)
references
References 33 publications
7
216
0
Order By: Relevance
“…To address these issues, we developed QuaID: a computational pipeline for analyzing SARS-CoV-2 wastewater sequencing data and inferring presence of VoCs. We use empirical results on real Houston wastewater data and simulated data to validate the efficacy of our software, and compare it to Freyja 4 , another state-of-the-art tool for VoC detection. Our key goal is achieving sensitivity to newly emerging variants in scenarios where coverage breadth and depth can be uneven, and the VoC-associated genomes are present at low abundances.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, we developed QuaID: a computational pipeline for analyzing SARS-CoV-2 wastewater sequencing data and inferring presence of VoCs. We use empirical results on real Houston wastewater data and simulated data to validate the efficacy of our software, and compare it to Freyja 4 , another state-of-the-art tool for VoC detection. Our key goal is achieving sensitivity to newly emerging variants in scenarios where coverage breadth and depth can be uneven, and the VoC-associated genomes are present at low abundances.…”
Section: Mainmentioning
confidence: 99%
“…Wastewater monitoring is an invaluable tool for SARS-CoV-2 surveillance [1][2][3][4][5][6][7][8] . Despite multiple recent successes in VoC monitoring and detection from wastewater sequencing data [9][10][11][12][13][14][15] , there are multiple challenges associated with the nature of the environmental data. Since wastewater represents a pooled sample of multiple hosts, it harbors a diversity of SARS-CoV-2 variants that are currently circulating in the population 1,2,10,13 , including potentially previously unreported genotypes 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical samples were sequenced from a selected hospital which is not representative of the Bangalore population. Karthikeyan et al 19 observed varying periods of VOC lineage detection relative to clinical genomic surveillance, which was attributed to different virus shedding characteristics across lineages 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on a 295 day comparison between wastewater and clinical sequences at the University of California, San Diego, a large collaborative effort likewise detected emerging variants of concern in wastewater samples up to two weeks before their identification in clinical samples, along with “multiple instances of virus spread not captured by clinical genomic surveillance.”5…”
Section: As Testing Wanes Sewage Picks Up the Slackmentioning
confidence: 99%